Upaya Radio Elbayu Mempertahankan Pendengar - Havisa, Jihan; Anggraeni, Taris; Baihaqi, Ilham; Naufal, Indra (Universitas Pendidikan Nasional, 2022)
Radio El Bayu is one of the AM radios that still exist today. This radio is also the only active radio station in Gresik. This radio, established in 1994, has a target audience of 40 years and over. In its time, this radio often held an event for the local community to build its image among the public. When many radios broadcast with FM, El Bayu remains consistent with the AM transmitter used. In fact, in Indonesia itself, it is very rare to find radio stations that still use this AM transmitter. Although the number of radio listeners has decreased, some people still choose to listen to radio channels. In this journal, we will discuss the efforts made by El Bayu Radio to retain radio listeners, considering that El Bayu still uses AM transmitters and has to compete with current digital media.